Editorial: Agile data-oriented research tools to support smallholder farm system transformation - Hammond, James; Pagella, Tim; Etten, Jacob van; Ghosh, Aniruddha; Wijk, Mark T. van (Frontiers Media, 2023)
Smallholder farming systems produce the majority of the food consumed in many lower- and middle-income countries and contribute significantly to national and local economies. However, a transformation is needed to deliver food security and decent incomes for the farmers themselves and to feed the growing populations within those countries. This transformation must be environmentally and socially sustainable to be successful in the long term. One obstacle is the lack of good quality, timely, and targeted information.